2020
DOI: 10.2169/internalmedicine.3616-19
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Effectiveness of Quadrivalent Influenza Vaccines by Distinguishing Between Influenza A (H1N1) pdm09 and Influenza A (H3N2) Using Rapid Influenza Diagnostic Tests During the 2018-2019 Season

Abstract: Objective To estimate the effectiveness of quadrivalent influenza vaccines during the 2018-2019 season for influenza A (H1N1) pdm09 and A (H3N2) in all age groups. Methods A test-negative case-control study was performed. Patients A total of 1,331 participants were divided into 4 groups (younger children: ! 6 years, older children: 7-15 years, younger adults: 16-64 years, and older adults: " 65 years). Results For all children, the adjusted vaccine effectiveness (VE) was significant against any influenza [41.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A total of 123 studies from 73 papers were included in the meta-analysis. Of these studies, 9 are RCTs [ 35 , 36 , 37 , 38 , 39 ] and 114 are TNDs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 123 studies from 73 papers were included in the meta-analysis. Of these studies, 9 are RCTs [ 35 , 36 , 37 , 38 , 39 ] and 114 are TNDs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the vaccine effectiveness. (QIV vaccine only [ 41 , 42 , 43 , 46 , 50 , 51 , 52 , 56 , 64 , 72 , 81 , 84 ]). …”
Section: Figurementioning
confidence: 99%
“…Consequently, adolescent individuals, after the development of primary immunity against H1N1 in childhood, might have suffered the original antigenic sin as similar H1N1 viruses presented as secondary infections. Research also reported that the VE of adolescents was much lower than other age groups during the same flu season [ 5 , 32 ], which may be due to the inability of pre-existing cross-reactive antibodies and vaccine-elicited antibodies to provide adequate protection [ 33 ]. Young adults and middle-aged individuals, age range 18–64 years, might have undergone less frequent vaccination compared with children [ 17 ] and might be infected by relatively distant genetic variants compared with prior antigens, and thus vaccine-induced immunity showed stronger responses to the matching of the vaccine virus.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the vaccine efficacy for preventing influenza virus infection overall and A/H1N1 specifically, is 29% and 44%, respectively; however, the vaccine efficacy for preventing A/H3N2 is only 9% [ 3 , 7 ]. In Japan, the vaccine efficacy for preventing influenza virus infection overall, and for A/H1N1, and A/H3N2 are 41.7%, 56.2%, and 34.5%, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%